Impact of gastric endoscopic submucosal dissection in elderly patients: The latest single center large cohort study with a review of the literature. Issue 11 (March 2019) - Yamaguchi, Hayato; Fukuzawa, Masakatsu; Kawai, Takashi; Matsumoto, Taisuke; Suguro, Maya; Uchida, Kumiko; Koyama, Yohei; Madarame, Akira; Morise, Takashi; Aoki, Yuki; Sugimoto, Akihiko; Yamauchi, Yoshiya; et al.
Abstract : Abstract: With the increase in the elderly population, we are witnessing an increase in the rate of patients with underlying diseases and those under treatment with antithrombotic drugs. In this study, we compared the treatment outcomes of endoscopic submucosal dissection (ESD) and other parameters in the following 3 groups: super-elderly, elderly, and nonelderly. Compared with the other groups, the super-elderly group showed a significantly higher incidence of underlying diseases and the rate of antithrombotic treatment ( P  < .05). However, we observed no significant difference in the rate of curative resection or incidence of complications among the 3 groups. ESD is a relatively safe technique when performed on super-elderly patients. However, we have identified some cases in the super-elderly group, for which ESD was selected as a minimally invasive treatment for lesions that did not meet the inclusion criteria for open surgery as well as for which follow-up observations were selected rather than additional surgery for noncurative resections. Further investigations concerning ESD are required, focusing on aspects such as indications, additional surgery, and informed consent of the patient or family, particularly when ESD is performed for super-elderly patients.